New deep-water cnidarian sites in the southern Adriatic Sea - ANGELETTI, L.; TAVIANI, M.; CANESE, S.; FOGLINI, F.; MASTROTOTARO, F.; ARGNANI, A.; TRINCARDI, F.; BAKRAN-PETRICIOLI, T.; CEREGATO, A.; CHIMIENTI, G.; MAČIĆ, V.; POLISENO, A. (Hellenic Centre for Marine Research, 2013)
Recent ROV (Remotely Operated Vehicle) exploration and bottom sampling in the southern Adriatic Sea (Apulian and Montenegrin margins) resulted in the discovery of cnidarian-rich deep-sea habitats in the depth range of ca. 400-700 m. In particular, ROV inspection of Montenegrin canyons reveals the existence of megabenthic communities dominated by a variety of cnidarians, including scleractinians (Madrepora oculata, Lophelia pertusa, Dendrophyllia cornigera), antipatharians (Leiopathes glaberrima) and gorgonians (Callogorgia verticillata) as major habitat forming taxa, often in association with sponges and, subordinately, serpulids. All such cnidarians are new records for the southeastern side of the Adriatic Sea. Our investigation indicates that an almost continuous belt of patchy cold water coral sites occurs along the entire southwestern margin (Apulian), basically connecting the Adriatic populations with those inhabiting the Ionian margin (Santa Maria di Leuca coral province).